Penerapan E-Comic Berbantuan Reading a Lot Berbasis PBL Upaya Peningkatan Sikap Kritis dan Kemampuan Menyimak Teks Aural - Zahrah P.B, Fadhwa Haifa; Purwati, Panca Dewi (YASIN, 2025)
Although listening skills and critical attitudes have received attention in several studies, research that specifically addresses the integration of e-comic media, the reading a lot strategy, and the Problem-Based Learning (PBL) model in Indonesian language instruction at the primary school level remains limited. This study aims (1) to describe the implementation of PBL-based e-comics supported by the reading a lot strategy as an effort to enhance the critical attitudes and aural text listening skills of fifth-grade students, and (2) to evaluate the effectiveness of these e-comics in improving both aspects. This study employed a mixed-methods approach with an explanatory sequential design, involving 14 fifth-grade students selected through total sampling. Data were collected using an Aural Comprehension Test (Tes Komprehensi Aural, TKA) in the form of multiple-choice and completion items, critical attitude observation sheets assessed by two observers, interviews, and documentation, and were analyzed using descriptive statistics and qualitative thematic analysis. The results indicate that the implementation of the PBL model supported by e-comics is effective in improving listening skills, as evidenced by an increase in classical mastery from 35.71% in the pretest to 92.86% in the posttest. Students’ critical attitudes also developed positively, as reflected in their ability to pose critical questions, express opinions logically, and relate the moral values of the stories to everyday life, with the majority of students falling into the good and very good categories. This study concludes that PBL-based e-comics supported by the reading a lot strategy play an important role in strengthening critical attitudes and aural text listening skills, and implies that teachers and schools can adopt them as an alternative model and medium for Indonesian language learning in primary schools to enhance student engagement and comprehension.